Desarrollo de un software educativo de la asignatura de computación para los alumnos de séptimo año de la escuela de educación básica “Torricelli” de la parroquia Urdaneta, cantón Saraguro, provincia de Loja, periodo lectivo 2013 – 2014 - Parra Chalán, Lupe del Carmen (2014)
In the present research word called "DEVELOPMENT OF AN EDUCATIONAL SOFTWARE FOR THE COURSE OF COMPUTING FOR STUDENTS SEVENTH YEAR OF SCHOOL EDUCATION BASIC" Torricelli "THE URDANETA CHURCH, CANTON SARAGURO, province Loja, ACADEMIC YEAR 2013 - 2014 ". Based on the needs to improve the teaching-learning process in the signature computation in the "Torricelli" school is the reason why I raise the overall objective: Develop an educational software computationally for seventh graders year of the School of Basic Education "Torricelli" parish Urdaneta, Saraguro canton province of Loja, academic year 2013 - 2014. " Also methods was used: inductive, deductive, analogical, scientific and comparative, to get the results data techniques and instruments such as the survey, interview and observation sheet, the same as those made to students was applied and the seventh year of teaching elementary school. With the acquisition of the data obtained in the survey of children was found that I 100% do not know any kind of educational software, as only didactic resources coditianos is used, so it would be necessary that the personnel ask anyone involved for the acquisition of new technological resources that enable actualizarce teaching with new technologies, that's why seeing the needs of the institution was carried out to create an Educational Software especially for the subject of computing. With the application of the validation of educational software, could introduce this new material berificando feasible, flashy, innovative technical aspect that has a good quality picture, sound, animations and presentations; serve as a pedagogical tool for teaching and it is of great potential dicáctico ready for use and handling.